SATISFACTION OF BANKING SERVICES BY SMALL ENTERPRISES IN LAKE CIPONDOH TOURIST DESTINATION TANGERANG FOR THE USE OF DIGITAL BANKING PRODUCTS AND THE IMPACT ON THE QUALITY OF BANKING SERVICES - Amrullah Amrullah; Heny Ratnaningtyas (Universitas Islam Lamongan, 2023)
This study aims to determine the effect of digital bank products on service quality through customer satisfaction. This type of research uses quantitative description. Total population is the same as the number of samples, namely 63 respondents. The results of the study show that: (1) Digital bank products have a significant effect on the quality of banking services; (2) Bank digital products have a significant effect on the satisfaction of banking services by small enterprises; (3) Quality of banking services has a significant effect on the satisfaction of banking services by small enterprises; (4) Bank digital products have a significant effect on the satisfaction of banking services by small enterprises through Quality of banking services.